Efektivitas Latihan Ladder Drill Terhadap Kecepatan Tendangan Sabit Atlet PPS Satria Muda Indonesia - Hikmatullah, Hikmatullah; Triprayogo, Rian; Zubaida, Ida (Jurnal Kepelatihan Olahraga, 2023)
This study aims to determine the effect of the ladder drill training method on sickle kick speed. Research using a quantitative approach to the experimental method. The population in this study were all 20 Indonesian Satria Muda PPS athletes using total sampling. Data collection techniques were carried out using field observations (observations), literature studies, and measurement tests by conducting pretest and posttest. The test is carried out by kicking the right and left legs with a sickle kick for 10 seconds. The amount of the contribution of the ladder drill exercise given to the speed of the men's sickle kick is 20% for the right leg and 16% for the left leg, while for women it is 19% for the right leg and 31% for the left leg, with t count = 6.398 t table = 2.100, while in the left sickle kick table data obtain t count 6.056 t table 2.100. Based on these data, it can be concluded that ladder drill training can increase the speed of the sickle kick of the PPS Satria Muda Indonesia Unit Serang City athlete